Development and Content Validation of the Psoriasis Symptoms and Impacts Measure (P-SIM) for Assessment of Plaque Psoriasis - Alice B. Gottlieb; Valerie Ciaravino; Christopher Cioffi; Luke Peterson; Richard B. Warren (Adis, Springer Healthcare, 2020)
Abstract Introduction Patients with plaque psoriasis experience a variety of signs and symptoms that can impact daily life, which may not be evaluated by clinician-reported outcomes. This study aimed to develop and assess the content validity of a new patient-reported outcome (PRO) measure to capture patient experiences of the signs, symptoms and impacts of psoriasis and aid integration of the patient perspective in treatment benefit-risk decision-making. Methods The psoriasis symptoms and impacts measure (P-SIM) was developed based on a literature search and interviews with five clinical experts in psoriasis to identify frequent signs, symptoms and impacts of psoriasis. Hybrid concept elicitation, cognitive debriefing and usability testing interviews were conducted with moderate to severe psoriasis patients to evaluate the content validity and patient understanding of the preliminary P-SIM. The preliminary P-SIM was refined using initial quantitative analyses of phase 2b data from psoriasis patients to inform the removal of any items. Results A preliminary 19-item P-SIM was developed for administration on a hand-held electronic tablet device using a 0-10 numerical response scale over a 24-h recall period. Patient interviews and testing demonstrated most patients interpreted the items and responses as intended, would not re-word any items, felt the responses matched the items and rated the device as easy to use. After quantitative testing, five items were removed from the preliminary 19-item measure because of conceptual overlap, floor effects and/or skewed distributions to generate the final 14-item P-SIM. Conclusions The P-SIM questionnaire has good content validity; patients reported it was easy to understand and reflective of their experiences. Following psychometric validation, the P-SIM may be a useful PRO measure for capturing the signs, symptoms and impacts of psoriasis and may support clinician-reported outcomes when assessing treatment benefits in clinical trials.